The fantasy of authenticity: touring with Lacan - Knudsen, Daniel C.; Rickly, J.M.; Vidon, Elizabeth S. (Elsevier, 2016)
Amidst the plethora of research regarding the meaning of authenticity, there remains uncertainty as to the work authenticity performs in tourism. Existential authenticity conceptually shifts focus from the objects of touristic practice to a sense of Being, suggesting that authenticity can be achieved, albeit only in the liminal moments of tourism experiences. Psychoanalysis would contend otherwise – authenticity will always be beyond our reach. In a 2006 publication, Tim Oakes broaches the topic when discussing authenticity as “an abyss”. We revisit that idea, developing it further through the lens of Lacanian psychoanalysis to argue that authenticity is a fantasy. It is not an empty concept, however, but like all fantasies authenticity does important work, particularly in tourism marketing and touristic motivation and experience. To better understand how authenticity as a fantasy fosters tourism desire, it is necessary to develop a conceptual understanding of alienation in relation to tourism motivation. This paper moves alienation from the periphery to the center of tourism theories, demonstrates the dialectical relationship of authenticity/alienation, and posits that as a fantasy authenticity is a malleable concept that has the ability to contextualize the “something” that is missing from our lives. As such, it will remain salient in tourism.